Synergistic Drive Between Local Knowledge and Landscape Design: Construction and Empirical Evidence of Landscape Design In-Situ Evaluation System for Forest Health Bases - Ya Chen; Yangtian Ye; Yun Ye (Buildings)
This study explores the intersection of landscape design and ecosystem services, emphasising context-sensitive design and the integration of indigenous and local knowledge (ILK) in forest health bases. Current challenges include disconnects between design practices and local cultural identity, as well as insufficient ecological integration, necessitating systematic approaches that harmonise ecological functions with sociocultural values. While existing research prioritises health benefit assessments, the role of ILK in long-term sustainability remains underexplored. To address this gap, we developed a multidimensional evaluation system integrating ecological, cultural, community, and human health indicators. Using a hybrid Delphi–Analytic Hierarchy Process (AHP), we identified 33 core indicators through literature word-frequency analysis. These indicators were refined via two rounds of expert surveys involving 48 interdisciplinary scholars and empirically validated at the Yuping Mountain Forest Health Base in Sichuan, China. The case study achieved an overall score of 4.371 (Grade I), with “Site location” (weight 0.064) and “Maintenance of the human landscape” (weight 0.056) as pivotal factors. ILK integration enhanced ecological resilience and community cultural engagement. Quantitative data revealed strong performance in five senses of experience (weight 0.056), though cultural resource utilisation requires refinement. The innovation of this study is that it is the first to construct an ILK-driven assessment framework to achieve the deep integration of scientific quantification and local wisdom. The study provides a decision-making tool that is both humanistic and scientific, in order to promote the synergistic development of human health, ecological protection, and cultural heritage and to help sustainable landscape design practice.